Innovative entrepreneurship evaluation in opinion of service company managers in Podlaskie Province - Elzbieta Skapska (Institute of Economic Research (IER), 2017)
The analysis of contemporary economies pursuing service based economies shows the issue concerning the innovation in services. It seems to be important from the standpoint of modifying the actions of enterprises and economies on competitive, local, national and international arenas. The economic practice and public activity prove there is a need for intelligent growth. It consists in the development of economy that is based on knowledge and innovation - the development which produces high added value. Thus, it is necessary to foster creative entrepreneurship that inclines towards the introduction of changes at the level of an enterprise which results in contributing to the creation of good economic condition in general. Research background: The article regards the issue of Podlaskie enterprises that tend to introduce innovation within the services of a higher level, understood as services, that creates added value from the point of view of service company managers. Purpose of the article: The aim of the article is to examine the opinions of managers from Podlaskie on innovation in services and whether the range of provided services is accepted by service receivers. Methodology/methods: The realization process of the assumed goal shall use the monograph and survey methods as well as analysis and synthesis. The survey is directed at managers of Polish companies in Podlaskie province. It regards factors that rule the inclination for the introduction of changes in service nature and its quality in the period of 1-3 years (stimulating and inhibitive). Findings & Value added: The research shows that the analyzed sub sector of services is an interesting area in the context of innovation in the micro scale and thus has potential for further study.
Keywords: D11; D33; D70; 330; service enterprises; innovations in services; service manager; Podlaskie Province